Psychoeducational Program on Anti-Bullying for Elementary School Students in Cimahi City - Asri, Afini Freudwi; Ermawati, Linda; Mediasari, Dita; Taufiq, Rachmat (LPPM Universitas Jambi, 2025)
Bullying remains a critical issue in Indonesian elementary schools, yet culturally adapted preventive interventions are still limited. This study aimed to implement and evaluate an anti-bullying psychoeducation program for elementary students in Cimahi City. Using a quasi-experimental pre–post design, the program was delivered to 40 students in grades 3 and 4 across two public schools. The intervention integrated cognitive instruction, emotional awareness activities, discussions, video demonstrations, and roleplay simulations, adapted from the Take A Stand framework. Data were collected through pre–post questionnaires measuring knowledge, empathy, and assertive bystander intentions, supported by qualitative observations and student reflections. Results showed substantial improvements across all domains: knowledge increased by 36.4%, empathy by 28.6%, and assertive intentions by 36.3%. Qualitative findings revealed enhanced emotional expression, stronger peer support, and greater willingness to seek help from trusted adults. The novelty of this study lies in its culturally contextualized, participatory psychoeducation model implemented within a semi-urban Indonesian setting. The program demonstrates that brief, SEL-based interventions can effectively enhance children’s cognitive and emotional competencies related to bullying. These finding highlight the importance of early psychological education and suggest that culturally tailored psychoeducation can serve as a scalable approach to fostering safer, more inclusive school environments